Sister species diverge in modality‐specific courtship signal form and function - Eileen A. Hebets; Mitch Bern; Rowan H. McGinley; Andy Roberts; Arik Kershenbaum; James Starrett; Jason E. Bond (Ecology and Evolution, 2021)
Abstract Understanding the relative importance of different sources of selection (e.g., the environment, social/sexual selection) on the divergence or convergence of reproductive communication can shed light on the origin, maintenance, or even disappearance of species boundaries. Using a multistep approach, we tested the hypothesis that two presumed sister species of wolf spider with overlapping ranges and microhabitat use, yet differing degrees of sexual dimorphism, have diverged in their reliance on modality‐specific courtship signaling. We predicted that male Schizocosa crassipalpata (no ornamentation) rely predominantly on diet‐dependent vibratory signaling for mating success. In contrast, we predicted that male S. bilineata (black foreleg brushes) rely on diet‐dependent visual signaling. We first tested and corroborated the sister‐species relationship between S. crassipalpata and S. bilineata using phylogenomic scale data. Next, we tested for species‐specific, diet‐dependent vibratory and visual signaling by manipulating subadult diet and subsequently quantifying adult morphology and mature male courtship signals. As predicted, vibratory signal form was diet‐dependent in S. crassipalpata, while visual ornamentation (brush area) was diet‐dependent in S. bilineata. We then compared the species‐specific reliance on vibratory and visual signaling by recording mating across artificially manipulated signaling environments (presence/absence of each modality in a 2 × 2 full factorial design). In accordance with our diet dependence results for S. crassipalpata, the presence of vibratory signaling was important for mating success. In contrast, the light and vibratory environment interacted to influence mating success in S. bilineata, with vibratory signaling being important only in the absence of light. We found no differences in overall activity patterns. Given that these species overlap in much of their range and microhabitat use, we suggest that competition for signaling space may have led to the divergence and differential use of sensory modalities between these sister species.